RELASIONAL BERPIKIR DENGAN BAHASA - Junifer Siregar (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2014)
This study wants to describe the relationship between the languages and mind in early childhood  and  want  to  describe  the  role  of  parents,  teachers,  and  the  environment  indeveloping  language  skills  and  thinking  in  early  childhood.  From  the  corner  of  thepsychology of early childhood development is a child who has limitations in the ability tothink and speak. At this stage the child's way of thinking, among others, still egocentric.Therefore  that  an  increase  in  the  child's  thinking,  activities  intended  to  enable  them  to perform classification, logical thinking, and trained to solve problem.They should also bestimulated to learn about a variety of concepts such as the concept of space, the concept oftime,  and  the  concept  of  number.  This  research  was  conducted  by  using  a  qualitative description.Activities that can stimulate a child's ability to think is to improve children's language abilities. The language used by the teacher is a language that raw organized yet simple and communicative.  But  in  early  childhood  development  to  date  is  not  known  precisely  themechanism  of  how  a  child  learns  a  language  so  that  the  language  can  be  learned.Based on the above, the authors are interested in doing research for "The RelationshipBetween Thinking With Speak In Childhood".Keywords : Thinking, speaking, and early childhood.